Pengaruh Transformational Leadership Dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior Melalui Komitmen Organisasi Sebagai Variabel Mediasi Pada Ypi. Ar-Rohman Cibinong Kab. Bogor - Khitara Aldilla Chandra (Jurnal Ilmiah Wahana Pendidikan, 2023)
Leadership behavior, job satisfaction, organizational commitment and organizational citizenship behavior, will eventually grow results in the form of satisfactory work performance or OCB. The results of a survey of OCB employees of educational foundations, both in terms of quality and quantity, were still not satisfactory. The quantity of output (amount produced) and the quality of output (output quality) show results and quality that are not optimal in carrying out work related to their duties and functions. The purpose of this study was to determine the effect of transformational leadership and job satisfaction on organizational citizenship behavior through organizational commitment as a mediating variable at the Islamic education foundation Ar-Rohman Cibinong, Bogor Regency. The total population in this study was 129 people with a saturated sampling method. In this study data collection was carried out by distributing questionnaires using the Likert scale data measurement method. The analytical technique used in this study was Structural Equation Modeling (SEM) with the AMOS 22.0 program. to calculate each variable. The results of the study revealed that transformational leadership had a positive and significant effect on organizational commitment, job satisfaction had a positive and significant effect on organizational commitment, organizational commitment had a positive and significant effect on OCB, transformational leadership had no positive and significant effect on OCB, job satisfaction had no positive and no effect significant to OCB, transformational leadership has no positive and insignificant effect on OCB which is mediated by organizational commitment, job satisfaction has no positive effect and not significant for OCB which is mediated by organizational commitment